Multiplexed detection of eight respiratory viruses based on nanozyme colorimetric microfluidic immunoassay - Wu, Feng; Cai, Defeng; Shi, Xueying; Li, Ping; Ma, Lan (Frontiers in Bioengineering and Biotechnology, 2024)
Pandemics caused by respiratory viruses, such as the SARS-CoV-1/2, influenza virus, and respiratory syncytial virus, have resulted in serious consequences to humans and a large number of deaths. The detection of such respiratory viruses in the early stages of infection can help control diseases by preventing the spread of viruses. However, the diversity of respiratory virus species and subtypes, their rapid antigenic mutations, and the limited viral release during the early stages of infection pose challenges to their detection. This work reports a multiplexed microfluidic immunoassay chip for simultaneous detection of eight respiratory viruses with noticeable infection population, namely, influenza A virus, influenza B virus, respiratory syncytial virus, SARS-CoV-2, human bocavirus, human metapneumovirus, adenovirus, and human parainfluenza viruses. The nanomaterial of the nanozyme (Au@Pt nanoparticles) was optimized to improve labeling efficiency and enhance the detection sensitivity significantly. Nanozyme-binding antibodies were used to detect viral proteins with a limit of detection of 0.1 pg/mL with the naked eye and a microplate reader within 40 min. Furthermore, specific antibodies were screened against the conserved proteins of each virus in the immunoassay, and the clinical sample detection showed high specificity without cross reactivity among the eight pathogens. In addition, the microfluidic chip immunoassay showed high accuracy, as compared with the RT-PCR assay for clinical sample detection, with 97.2%/94.3% positive/negative coincidence rates. This proposed approach thus provides a convenient, rapid, and sensitive method for simultaneous detection of eight respiratory viruses, which is meaningful for the early diagnosis of viral infections. Significantly, it can be widely used to detect pathogens and biomarkers by replacing only the antigen-specific antibodies.